Bhiṣvā Stūpa of Birgunj as an 'Ancient Stūpa' - Ranjitkar, Junu Basukala (Historical Journal, 2023)
An earthen mound, Bhiṣvā located on Birgunj, where Buddhist pilgrims stayed during the night between their journey from Lumbini and Bodhgaya. During the Rana period, Ranas assumed a trove of treasure and jewellery inside the earthen mound in the Terai region, excavated it, found ancient bricks and coals, and then left the digging of the hill. A sculptor expert from the Archaeology Department of Nepal declared the earthen mound Bhiṣvā stupa in 1977 without any scientific investigation. Later, Two Buddhist priests worshipped jivanyāsapūjā on the stūpa in 1978. After that, Hindu and Buddhist followers installed different Hindu and Buddhist images on the stupa at various times. The Department of Archeology has not done any research on it and has not declared it as a Stupa. It cannot be called a stupa without the declaration of an official institution, without mention in any Buddhist scriptures, and without any authentic document based on the words of people. But it can be called a stupa based on its shape and name.